Determination of Water Pollution of River Ganga during Lockdown Period - Nazia Hasan; Rakesh Prasad; Arafat Ahmad (New Visions in Biological Science Vol. 5, 2021)
In the present study, an effort was made to study the water quality of river Ganga and the effect of lockdown on the physicochemical characteristics of the river water in the state of Bihar. The aim of the study was to check the water quality of the Ganges during the lockdown period and to analyse the impact of the situation on the quality of the water of the Ganges with special reference to a few areas in Bihar, where domestic sewage, agricultural wastes and air pollution affecting the river water are considered to be the major source adding to the river pollution. Exploratory research design has been used in which both primary and secondary data was collected. The primary data has been collected thrice in the month of March and April from the sampling stations of Digha (Patna), Arrah (Bhojpur) and Aami (Saran) sites of the Ganges in Bihar. The data was further analysed to test pH, Dissolved Oxygen (DO), Biological Oxygen Demand (BOD), Total Coliform (TC) and Faecal Coliform (FC). It has been found that there was no major improvement in the existing quality of the river during the lockdown period. It is very evident that the decrease in water pollution of river Ganga has been found mostly in the industrial areas as compared to the non-industrial ones. In non-industrial areas, not much improvement has been seen because the domestic waste dumping did not stop and even increased in maintenance of hygiene.